WORLD READING: STRENGTHS BETWEEN AN OUTREACH PRACTICE AND THE PRINCIPLES OF CRITICAL PEDAGOGY - Santana, Leyla Menezes de (2018)
This article aims to analyze elements of the experience lived bases on a hands on practice inspired by the principles in Critical Pedagogy. We try to answer in what way the principles of this Pedagogy were experienced in the scope of the Reading the World outreach project. Based on a qualitative approach, we use narratives of the students who participated in the above mentioned educational practice as adult literacy teachers. We realize that the Freirean postulates have proved important, proving not only in theory but also in practice that knowledge is only liberating if it is associated with a political commitment on behalf of the oppressed.